Application of the Make a Match Model in Elementary Mathematics Learning Outcomes: Penerapan Model Make a Match pada Hasil Belajar Matematika Siswa Sekolah Dasar - Alfiqri Agi, Muhamad; Wahyu Hidayat, Puput; Hamzah, Iri (Indonesian Journal of Innovation Studies, 2025)
General background: Mathematics is a fundamental discipline crucial for students’ cognitive development, yet many elementary school students in Indonesia continue to struggle with low achievement due to teacher-centered and monotonous instruction. Specific background: At SD Negeri 205/II Bangun Harjo, most fifth-grade students failed to reach the minimum mastery criteria in mathematics, indicating an urgent need for innovative learning models. Knowledge gap: Although cooperative models like Make A Match have been studied in various contexts, empirical evidence on their effectiveness in mathematics learning at the elementary level, particularly in rural settings, remains limited. Aims: This study aimed to analyze the application of the Make A Match model in improving students’ mathematics learning outcomes. Results: Using a pre-experimental one-group pretest–posttest design with 11 participants, results revealed an increase in average scores from 56.36 (pretest) to 72.12 (posttest), while learning completeness rose from 27.27% to 63.63%. A paired samples t-test confirmed a statistically significant improvement (p = 0.012 < 0.05). Novelty: The study provides contextual evidence of Make A Match effectiveness in an underrepresented elementary school setting, complemented by rigorous instrument validation. Implications: These findings highlight the model’s potential as an engaging and practical strategy to foster active participation, collaboration, and better mathematics learning outcomes in primary education. Highlight: • Significant improvement in average scores and mastery level after applying Make A Match. • Novel contribution by providing empirical evidence in rural elementary school context. • Practical implications for teachers to adopt interactive and enjoyable strategies. Keywords: Make A Match, Mathematics Learning, Cooperative Model, Learning Outcomes, Elementary Education